The Musicality of Narrative Film - Kulezic-Wilson, D. author. aut Link
X, 220 p.
Keywords: The Musicality of Narrative Film is the first book to examine in depth the film/music analogy. Using comparative analysis, Kulezic-Wilson explores film's musical potential, arguing that film's musicality can be achieved through various cinematic devices, with or without music.